Superheated Steam Drying of Cashew Kernels with Testa - Rashid Eang (2018)
© 2017 The Authors. Published by Elsevier Ltd. Thermal processing of cashew kernels is determined by removal of moisture, and therefore, an indication of the product quality and the entire process economics. This paper reported an improved design of superheated steam drying system for cashew kernels with the objective of determining the drying characteristics and the effect of superheated steam on product quality. The range of drying steam temperature at atmospheric pressure was 120- 140°C with velocity varied from 1-3 m/s. The total colour difference and browning index were used to examine the change in colour of dried kernels. The results showed that higher temperature and velocity of steam promoted higher drying rate and lower final moisture content of the product. The high temperature of steam was found to be the major cause of colour degradation of dried kernel besides steam velocity.